2014
DOI: 10.1016/j.ymgmr.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing reveals compound heterozygous mutations in SLC19A3 causing biotin-thiamine responsive basal ganglia disease

Abstract: Biotin-thiamine responsive basal ganglia disease (BTBGD) is a rare metabolic condition caused by mutations in the SLC19A3 gene. BTBGD presents with encephalopathy and significant disease progression when not treated with biotin and/or thiamine. We present a patient of Mexican and European ancestry diagnosed with BTBGD found to have compound heterozygous frameshift mutations, one novel. Our report adds to the genotype-phenotype correlation, highlighting the clinical importance of considering SLC19A3 gene defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The follow-up MRI after 1-6 months showed resolved lesions after treatment. Genetic testing in those patients revealed mutation of the SLC19A gene in agreement with Karimzadeh [4], Alabdulqader et al [5], and Sremba et al [7] who reported similar MRI imaging findings and genetic testing results and concluded that the typical MRI finding, lack of clinical improvement, and the clinical suspicion should raise the possibility of BTBGD, so empirical treatment should started.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The follow-up MRI after 1-6 months showed resolved lesions after treatment. Genetic testing in those patients revealed mutation of the SLC19A gene in agreement with Karimzadeh [4], Alabdulqader et al [5], and Sremba et al [7] who reported similar MRI imaging findings and genetic testing results and concluded that the typical MRI finding, lack of clinical improvement, and the clinical suspicion should raise the possibility of BTBGD, so empirical treatment should started.…”
Section: Discussionsupporting
confidence: 73%
“…The disease is characterized by early onset encephalopathy (usually below the age of 4 years). In many case reports, febrile illness preceded the manifestation disease; this febrile illness progresses to severe disability, dystonia, ataxia, seizures, and death if the patients were not treated with biotin and thiamine supplements [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The infantile-onset progressive neurodegeneration and bilateral, symmetrical abnormalities in the basal ganglia found in HIBCH deficiency are typical of Leigh syndrome, which is a genetically and clinically heterogeneous entity [4,20]. In addition to HIBCH, other inborn errors of metabolism, including pyruvate dehydrogenase complex (PDHC) deficiency [8], biotin-thiamine basal ganglia disease [21], pyruvate carboxylase [22,23] and SCEH deficiencies [10], mirror the radiological findings associated with Leigh syndrome. These clinical similarities caused by multiple independent genetic etiologies highlight the importance of comprehensive diagnostic testing, including acylcarnitine analysis, in the clinical work-up of patients presenting with Leigh’s disease.When biochemical investigations are negative or inconclusive, NGS gene panels that include HIBCH or WES may be reasonable approaches.…”
Section: Discussionmentioning
confidence: 99%
“…5 Most of the patients with this category were unresponsive to biotin and thiamine supplementation and died early. [29][30][31][32][33] However, two reports in the literature showed favorable response to biotin and thiamine administration from this subtype. 5 B. Atypical infantile spasms: In 2010, Yamada et al 6 reported four Japanese patients whom neurological symptoms started to appear at 1 to 2 months and started to have atypical infantile spasms at the age ranging from 2 to 11 months.…”
Section: Metabolic Pathwaymentioning
confidence: 95%
“…22 Patients with the early-onset Leigh-like form suffer from homozygous nonsense mutations, homozygous missense mutations, compound heterozygous deletions or duplications. 5,29,[31][32][33]36 Genotype-phenotype correlations for SLC19A3 gene defects are poor and incomplete. However, it seems that the founder Middle Eastern mutation is associated with the milder phenotype and late onset (i.e., the classical childhood BTBGD form).…”
Section: Geneticsmentioning
confidence: 99%